The Consequences of Altruistic Behavior in Three Selected Picture Books - Rahmita Egilistiani; Ratu Prayuana; Citra Fatimah (STKIP PGRI Bandar Lampung, 2025)
Altruism is commonly presented in children’s literature as a fundamental moral virtue that encourages kindness, empathy, and prosocial behavior. However, literary representations of altruism often prioritize its positive moral outcomes while overlooking the emotional, psychological, and social consequences experienced by those who perform altruistic acts. This study examines the consequences of altruistic behavior in three selected picture books: Little Miss Mary and the Big Monster Makeover by G. G. Toropov and Cleone Cassidy (2008), Harold Loves His Woolly Hat by Vern Kousky (2018), and My Brother’s Wheeeeelchair by Salil Chaturvedi (2019). Employing a qualitative interpretative research design, this study conducts close textual and visual analysis to explore how altruistic behavior is constructed and how its consequences are represented within narrative and illustrative elements. The findings reveal that altruistic behavior in these picture books generates complex outcomes, including emotional vulnerability, identity negotiation, and sustained social responsibility. While altruistic actions promote empathy, acceptance, and inclusion, they also expose characters to emotional risk, personal sacrifice, and moral obligation. These findings challenge idealized portrayals of altruism as an uncomplicated moral good and highlight the pedagogical potential of picture books to present ethical values in nuanced and emotionally realistic ways. This study contributes to children’s literature scholarship by offering a critical perspective on moral representation and emphasizing the importance of acknowledging the emotional dimensions of altruistic behavior in narratives for young readers.